Design of functional nanoparticles by microfluidic platforms as advanced drug delivery systems for cancer therapy. Issue 5 (17th January 2023) - Fabozzi, Antonio; Della Sala, Francesca; di Gennaro, Mario; Barretta, Marco; Longobardo, Gennaro; Solimando, Nicola; Pagliuca, Maurizio; Borzacchiello, Assunta
Abstract : Nanoparticle systems are functional carriers that can be used in the cancer therapy field for the delivery of a variety of hydrophobic and/or hydrophilic drugs. Abstract : Nanoparticle systems are functional carriers that can be used in the cancer therapy field for the delivery of a variety of hydrophobic and/or hydrophilic drugs. Recently, the advent of microfluidic platforms represents an advanced approach to the development of new nanoparticle-based drug delivery systems. Particularly, microfluidics can simplify the design of new nanoparticle-based systems with tunable physicochemical properties such as size, size distribution and morphology, ensuring high batch-to-batch reproducibility and consequently, an enhanced therapeutic effect in vitro and in vivo . In this perspective, we present accurate state-of-the-art microfluidic platforms focusing on the fabrication of polymer-based, lipid-based, lipid/polymer-based, inorganic-based and metal-based nanoparticles for biomedical applications.